Respuesta :

Answer:

For First Solution: [tex]y_1(t)=e^t[/tex]

[tex]y_1(t)=e^t[/tex] is the solution of equation y''-y=0.

For 2nd Solution:[tex]y_2(t)=cosht[/tex]

[tex]y_2(t)=cosht[/tex]  is the solution of equation y''-y=0.

Step-by-step explanation:

For First Solution: [tex]y_1(t)=e^t[/tex]

In order to prove whether it is a solution or not we have to put it into the equation and check. For this we have to take derivatives.

[tex]y_1(t)=e^t[/tex]

First order derivative:

[tex]y'_1(t)=e^t[/tex]

2nd order Derivative:

[tex]y''_1(t)=e^t[/tex]

Put Them in equation y''-y=0

e^t-e^t=0

0=0

Hence [tex]y_1(t)=e^t[/tex] is the solution of equation y''-y=0.

For 2nd Solution:

[tex]y_2(t)=cosht[/tex]

In order to prove whether it is a solution or not we have to put it into the equation and check. For this we have to take derivatives.

[tex]y_2(t)=cosht[/tex]

First order derivative:

[tex]y'_2(t)=sinht[/tex]

2nd order Derivative:

[tex]y''_2(t)=cosht[/tex]

Put Them in equation y''-y=0

cosht-cosht=0

0=0

Hence [tex]y_2(t)=cosht[/tex]  is the solution of equation y''-y=0.

The functions [tex]y(t)=e^t[/tex] and [tex]y(t)=cosht[/tex] are solutions of given differential equation.

We have to prove that given function is a solution of the differential equation.

Given function,   [tex]y(t)=e^t[/tex]

Given differential equation are, [tex]y''-y=0[/tex]

  So that,  [tex]y'(t)=e^t , y''(t)=e^t[/tex]

Substitute values in given differential equation.

                    [tex]e^t - e^t=0[/tex]

Thus, function [tex]y(t)=e^t[/tex] is solution of given differential equation.

Another function is,  [tex]y(t)=cosht[/tex]

So that,  [tex]y'(t)=sinht , y''(t)=cosht[/tex]

Substitute values in given differential equation.

                    [tex]cosht-cosht=0[/tex]

Thus, function [tex]y(t)=cosht[/tex] is solution of given differential equation.

Learn more:

https://brainly.com/question/1164377